Fairy Ponies rainbow races - Davidson, Zanna (Not Known, 2014)
Holly can't wait to watch her friend Puck, the fairy pony, compete in the Rainbow Races. But when an enchanted storm is unleashed over Pony Island, ruining the races, the home of the fairy ponies is threatened with darkness for ever...